(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, according to the differential manifestation of ethnic stereotypes and psychological institutions of Uzbek and Kyrgyz girls, the content of mastering family etiquette, self-management, rational assessment of the situation, and patience in the face of difficulties it is justified that the readiness for the family is reached through the acquisition. According to the expression of ethnic stereotypes and psychological institutions of Uzbek and Kyrgyz girls, social values, interpersonal emotional and cognitive behavioral components have been proven to be social-psychological characteristics that determine the influence of the level of readiness for family life.